A History of Scientific Archeological Research by the Imperial Archeological Commission in Samarkand - Makhmudkhon Yunusov; Olimjon Iriskulov (International Journal on Integrated Education, 2022)
This research will consider: The beginning of the study of Central Asia by the Imperial Archaeological Commission, includes the expedition of P.Lerch to Yangikent, Turkestan, Shymkent, Tashkent, Khojand and Uratepa in Central Asia;The first scientific study of Afrosiab; N. Veselovsky's dispatch to Central Asia in 1885 the acquisition of the first scientific data on the ancient cities of Central Asia, in particular of Samarkand, and the accumulation of a large archaeological collection;organization of a scientific-architectural expedition to Samarkand under the leadership of N.Veselovsky to complete a systematic study of architectural monuments in 1895-1896 that resulted in, the publication of the album "Samarkand Mosques";the historical, archaeological, linguistic and ethnographic study of Turkestan; and excavations conductedby American scientists Rafael Pompelli and Hubert Schmidt near Gaur-Kala (the arch of the ancient city of Merv) and Annau under V.Barthold’s observation. The Commission's efforts to address the problems of protection, study, and archeological research of monuments in the empire, including Samarkand show how the Commission shaped the standards for archaeology and the focus of research. This rich history presents the ways that the state affected public knowledge of the past.